MAKNA SPIRITUAL â€œKLIWONANâ€ PADA MAKAM SUNAN KALIJAGA KADILANGU- DEMAK - Marwoto, Marwoto (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2018)
Abstract: The tomb of Sunan Kalijaga has a sacred nature for the pilgrims. The existence of the background story, legend and even myth makes the tomb brought many pilgrims from various quarters because the belief will be able to bring blessing to the life of the community. The strength of the grave artifact of a religious figure (Wali) indicates to certain people who still believe in a supernatural relationship, thus assigning value to the sacred place. The position of the tomb has an important meaning is to give impact on the pilgrims of life activities. Every Friday Kliwon the tomb of Sunan Kalijaga has significance in the eyes of the pilgrims. The research method is descriptive based on observations and interviews of pilgrim respondents. The results of research on the tomb of Sunan Kalijaga explain about the relation of transcendental ritual between the pilgrims with the object of the tomb.Â Keyword: Religious Pilgrimage, Spiritual, Tomb of Saints, Friday of KliwonÂ Abstrak: Makam Sunan Kalijaga memiliki sifat sakral bagi para peziarah. Adanya latar cerita sejarah, legenda bahkan mitos menjadikan makam tersebut banyak mendatangkan para peziarah dari berbagai kalangan karena keyakinan akan dapat membawa keberkahan terhadap kehidupan masyarakatnya. Kekuatan artefak makam dari seorang tokoh religius (Wali) mengindikasikan pada masyarakat tertentuÂ masih yang percaya pada hubungan yang bersifat supranatural, sehingga memberi nilai dengan sebutan tempat keramat. Kedudukan makam memiliki arti penting yaitu memberikan dampak pada para peziarah terhadap aktivitas kehidupannya. Setiap Jumat Kliwon makam Sunan Kalijaga memiliki arti penting di mata para peziarah. Metoda penelitian bersifat deskriptif berdasarkan pengamatan dan hasil wawancara terhadap responden peziarah. Hasil riset pada makam Sunan kalijaga menjelaskan tentang hubungan ritual yang bersifat transendental antara para peziarah dengan objek makamÂ Kata Kunci: Ziarah Religi, Spiritual, Makam Wali, Jumat Kliwon